RAF/MEK/extracellular signal–related kinase pathway suppresses dendritic cell migration and traps dendritic cells in Langerhans cell histiocytosis lesions - Hogstad, Brandon (J Exp Med, 2018)
Langerhans cell histiocytosis (LCH) is an inflammatory myeloid neoplasia characterized by granulomatous lesions containing pathological CD207(+) dendritic cells (DCs) with constitutively activated mitogen-activated protein kinase (MAPK) pathway signaling. Approximately 60% of LCH patients harbor somatic BRAFV600E mutations localizing to CD207(+) DCs within lesions. However, the mechanisms driving BRAFV600E(+) LCH cell accumulation in lesions remain unknown. Here we show that sustained extracellular signal–related kinase activity induced by BRAFV600E inhibits C-C motif chemokine receptor 7 (CCR7)–mediated DC migration, trapping DCs in tissue lesions. Additionally, BRAFV600E increases expression of BCL2-like protein 1 (BCL2L1) in DCs, resulting in resistance to apoptosis. Pharmacological MAPK inhibition restores migration and apoptosis potential in a mouse LCH model, as well as in primary human LCH cells. We also demonstrate that MEK inhibitor-loaded nanoparticles have the capacity to concentrate drug delivery to phagocytic cells, significantly reducing off-target toxicity. Collectively, our results indicate that MAPK tightly suppresses DC migration and augments DC survival, rendering DCs in LCH lesions trapped and resistant to cell death.